KAJIAN TEKNOLOGI IMPROVED BCL UNTUK MEMPODUKSI BBM SINTETIS - Lambok Hilarius Silalahi (Jurnal Energi dan Lingkungan (Enerlink), 2005)
An overview of Coal Liquefaction technology, so called Improved Brown Coal Liquefaction or Improved BCL process is discussed. The improved BCL process is actually the most effective process to obtain high oil yield compared with other coal liquefaction processes and well suited to most Indonesian coal. The process has been confirmed with Banko coal taken from Tanjung Enim, Sumatra and the process design as well as the conceptual design for feasibility study has been made. In this paper, an overview of features of the improved BCL process is introduced along with the typical result of coal liquefaction test. Moreover, a description of Hycol process, to gasify brown coal efficiently to produce hydrogen gas is discussed. This process has been demonstrated in a 150 t/d demo plant in Japan to confirm the engineering performance as well as the thermal efficiency. Finally the result of economic viability is presented to calculate the overall cost including pipeline cost and transportation cost of the equipment.Kata kunci:Â Improved BCL process, coal liquefaction technology,Â Indonesian coal